2005
DOI: 10.1128/jvi.79.14.9206-9216.2005
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Pancreatic Necrosis Virus VP5 Is Dispensable for Virulence and Persistence

Abstract: Infectious pancreatic necrosis virus (IPNV) is the causative agent of infectious pancreatic necrosis (IPN)disease

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
64
1
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 50 publications
4
64
1
3
Order By: Relevance
“…In case of IPNV, Hong et al (19) reported that VP5, a nonstructural protein, inhibits the apoptosis of virus-infected cells. However, Santi et al (37) reported that VP5 is dispensable for the growth of IPNV, which suggests the possibility that VP5 is not the only factor for the inhibition of apoptosis in IPNV-infected cells. In this study, we showed that IPNV infection increased the expression of a cellular protein, salmon annexin 1 and that the increased expression of salmon annexin 1 inhibits the apoptosis of IPNV-infected cells and supports the growth of IPNV in cells.…”
Section: Discussionmentioning
confidence: 99%
“…In case of IPNV, Hong et al (19) reported that VP5, a nonstructural protein, inhibits the apoptosis of virus-infected cells. However, Santi et al (37) reported that VP5 is dispensable for the growth of IPNV, which suggests the possibility that VP5 is not the only factor for the inhibition of apoptosis in IPNV-infected cells. In this study, we showed that IPNV infection increased the expression of a cellular protein, salmon annexin 1 and that the increased expression of salmon annexin 1 inhibits the apoptosis of IPNV-infected cells and supports the growth of IPNV in cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, to study the role of VP5 protein in virulence of IPNV, we recovered three viruses: one encoding a truncated 12-kDa VP5 (rNVI15), another encoding a full-length 15-kDa VP5 (rNVI15-15K), and one lacking the expression of VP5 (rNVI15-⌬VP5). All three viruses are virulent and cause Ͼ80% mortality in Atlantic salmon smolts, suggesting that VP5 is not directly involved in the virulence of IPNV (32).…”
mentioning
confidence: 99%
“…This protein has been detected in infected cells; however, it is not essential for virus replication in vitro (22,36). Recently, it has been shown that this protein is dispensable for viral replication in vivo, and it is not involved in persistent infection or virulence of the virus (32). Segment B encodes a 94-kDa protein, VP1, which functions as the virion associated RNA-dependent RNA polymerase (7,9).…”
mentioning
confidence: 99%
“…Özellikle yavru ve genç salmonid balıklarda yüksek mortalite ile seyreder. Etken, RNA grubundan Aquabirnavirüs ailesinde IPN virüsü (IPNV)'dür (4,9,18,20).…”
Section: Introductionunclassified